Relationship between nucleotide-binding oligomerization domain-containing protein 2 variants and severity of acute pancreatitis - Harputluoglu, M. M. M.; Ozbek, M.; Demirel, U.; Otlu, B.; Yener, O.; Gursoy, N. C.; Dertli, R. (Univ Catholique Louvain-Ucl, 2019)
Background and aim : Intestinal bat tier dysfunction has been implicated in the development of infectious complications of acute pancreatitis. Nucleotide-Binding Oligomerization Domain- Containing Protein 2 (NOD2) plays an important role in the proper functioning of intestinal defense mechanisms. Here, we investigated the frequency of NOD2 variants in patients with mild and severe acute pancreatitis. Materials and Methods : Groups 1, 2 and 3 comprised healthy participants and patients with mild and severe pancreatitis, respectively. Four NOD2 variants and serum interleukin-6 (IL-6), Tumor Necrosis Factor-a (TNF-a) and lipopolysaccharide-binding protein (LBP) levels were analyzed. Results: Three patients (3/32, 9.4%) in the severe pancreatitis group were positive for the p.R702W valiant. This valiant was negative in other groups. One, three and three patients in the healthy (1/27,3.7%), mild (3/36,8.3%) and severe pancreatitis (3/32, 9.4%) groups tested positive for the 1007fs variant, respectively. No significant difkrences in the frequencies of NOD2 variants were evident among the groups. Serum IL-6, TNF-a and IMP levels were markedly higher in the severe pancreatitis than the healthy and mild pancreatitis groups (all p<0.091). We observed no significant correlation between cytokine levels and NOD2 variants. Conclusion : Our results support an association between the presence of the p.R702W variant and severe pancreatitis.
Keywords: Mucosal immunity; inflammation; cytokines; acute pancreatitis